PENGARUH HARGA DAN CITRA MEREK TERHADAP VOLUME PENJUALAN MAKANAN DAN MINUMAN PADA WARKOP BUNDU TALASALAPANG MAKASSAR - Warda Amalia (Prodi Manajemen Universitas Syekh Yusuf Al Makassari Gowa, 2023)
This study aims to determine the effect of price and brand image on sales volume of food and beverages at Warkop Bundu Talasalapang. The population in this study were Warkop Bundu consumers, namely 985 people with a total sample taken in this study as many as 91 people. The sampling technique uses the slovin formula. This study uses a quantitative method, where the data collection method used is by means of observation, questionnaires, and documentation. The analytical method used is Validation Test, reliability test, multiple regression analysis and partial test. The results of this study indicate that the price variable has a significant effect on sales volume. Brand image has a significant effect on sales volume. Based on the results of this study, it is hoped that warkop Bundu Talasalapang will maintain affordable prices, and be able to continuously improve the brand image they have in maintaining sales volume because all the independent variables, namely price and brand image in this study affect sales volume.